Klausa yang Digunakan dalam Media Siber Infoindonesia.id - Nugraha, Defrizal Ahmad; Nadra, Nadra; Noviatri, Noviatri (Puitika, 2023)
This research aims to examine the types of clauses used in the cyber media Infoindonesia.id. There are three stages in this research; the data provision stage, the data analysis stage, and the data analysis presentation stage. At the data provision stage, the observation method is used. At the data analysis stage, the referential equivalent method is used. At the presentation stage of the data analysis results, the informal presentation method is used. Based on the data on the clauses used in the Infoindonesia.id cyber media, there are various types of clauses. The types of clauses are clauses based on their internal structure, clauses based on the presence or absence of negative words that grammatically negate P, and clauses based on the category of words that occupy the function of P. Clauses based on their internal structure, clauses consist of complete clauses and incomplete clauses. Based on whether there are negative words that grammatically negate P, the clause consists of positive and negative clauses. Based on the category of words that occupy the P function, clauses consist of noun clauses, verb clauses, numeral clauses, and preposition clauses. Verb clauses themselves have several types, namely active verb clauses, intransitive verb clauses, passive verb clauses, verb clauses, adjective verb clauses, reflexive verb clauses, and reciprocal verb clauses.